STRATEGI PENGELOLAAN ZAKAT, INFAK, SHADAQAH, WAKAF (ZISWAF) OLEH BAITULMAAL MUNZALAN INDONESIA (BMI) DI SAMARINDA - Imanuddin, Imanuddin (At-Tawazun, Jurnal Ekonomi Syariah, 2024)
This research aims to determine the management strategy for Zakat, Infaq, Sadaqah, and Waqf (ZISWAF) by Baitulmaal Munzalan Indonesia (BMI) in Samarinda in collecting and distributing ZISWAF. This type of research is field research with a qualitative descriptive approach. Data collection techniques in this research are interviews, observation, and documentation. The data analysis used is descriptive-qualitative, through three stages, namely data reduction, data presentation, and conclusions. The results of this research show that the fundraising strategy creates interesting and creative programs to attract donors (Muzakki). ZISWAF fundraising is carried out through various interesting programs such as the Rice Donation Movement, the Happy Friday Program, and the Prize Program for Muslimah, which aims to invite Muzakki and foster parents to participate in distributing their funds without any element of coercion. Meanwhile, the distribution of ZISWAF funds covers three main areas, namely education, social humanity, and the economy. The ZISWAF fund distribution process strategy is carried out in selective stages, namely through socialization, survey, and networking stages, to ensure that assistance is right on target and beneficial for Mustahik.